Mycobiota and toxigenecity profile of Aspergillus flavus recovered from food and poultry feed mixtures in Cameroon - Kana, J.R.; Gnonlonfin, G.J.B.; Harvey, Jagger J.W.; Wainaina, J.; Wanjuki, I.; Skilton, Robert A.; Teguia, A. (2013)
A total of 202 poultry feed and its raw ingredients collected from different agroecological zones of Cameroon were examined for total mycoflora and the ability of A. flavus isolates to produces aflatoxin B1. Dilution plating was used for fungal isolation. The mean fungal contamination levels were significantly higher in maize and peanut meal as compared with broiler and layer feeds. In peanut meal and poultry feed, the most representative fungi were A. flavus, A. niger, A. oryzae, F. solani, F. verticilloides, Penicillium spp, and Rhizopus spp. Of all the fungi encountered, A. flavus was encountered in 90% of white maize and 28.5% of yellow maize samples. The frequency of isolation of the most representative fungi in peanut meal, broiler and layer feed was 100, 94, and 76.5% for A. flavus and 70.6, 82.3, and 76.5% for Penicillium spp, respectively. Molecular identification using the Intergenic Spacer Gene (IGS) for aflatoxin biosynthesis confirmed all fungi identified morphologically as A. flavus. Aflatoxin B1 analysis showed that all the A. flavus isolates encountered were aflatoxin B1 producers. Conclusion from this study indicate that the use of peanut meal in poultry feed is risky, and can impact poultry health and economic benefits.